Gambaran Kelayakan Kamar Gelap Di Rsu Vina Estetika Description Of The feasibility Of A Dark Room At Rsu Vina Estetika - Jonas, Jonas (Impression : Jurnal Teknologi dan Informasi, 2022)
The dark room is an important room in a Radiology Installation which is useful as a place for film processing, storage of unexposed film, storage and maintenance of cassettes and screens, as a place for the initial and final processes of making radiographs. This process plays an important role because it affects the quality of the resulting radiograph. Darkroom equipment must meet the standards of the Republic of Indonesia Minister of Health Regulation No. 24 of 2020, so periodic inspections must be carried out in the darkroom to produce an optimal picture of the film processing process. This research aims to determine the standardization of the darkroom in the radiology installation at RSU Vina Estetika. This research is a type of qualitative descriptive research. The research was conducted at RSU Vina Estetika from April to May 2022. Data processing was carried out by means of field observations, in-depth interviews with radiographers and documentation. The object of this research is a dark room while the research target is a radiographer. In this research, the results showed that at RSU Vina Estetika there were several darkroom components that did not meet standards, such as the darkroom construction on the ceiling, ventilation, general lighting, and the absence of a cassette hatch. Meanwhile, the darkroom floor, darkroom work layout, darkroom equipment, darkroom location and water circulation in the darkroom have met standardization.